2001-2002 Comparative Citrus Budgets - Ronald P. Muraro (EDIS)
This is EDIS document FE 350, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published February 2003.